2016
DOI: 10.1080/09540121.2016.1146207
|View full text |Cite
|
Sign up to set email alerts
|

Depression and HIV risk among men who have sex with men in Tanzania

Abstract: Studies have shown high rates of depression among men who have sex with men (MSM) in developed countries. Studies have also shown association between depression and HIV risk among MSM. However, very little research has been done on depression among African MSM. We assessed depression and HIV risk among a sample of MSM in Tanzania. We reviewed data on 205 MSM who were recruited from two Tanzanian cities using the respondent driven sampling method. Demographic and behavioral data were collected using a structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 40 publications
4
46
0
1
Order By: Relevance
“…These findings are similar to other studies from the metropolitan city of Dar es Salaam, Tanzania, where MSM reported high levels of alcohol abuse, commercial sex work, and stigma in healthcare [ 1 , 5 , 6 ]. In our study, men expected partners to be involved in multiple concurrent partnerships, and also they themselves engaged in simultaneous sexual relations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are similar to other studies from the metropolitan city of Dar es Salaam, Tanzania, where MSM reported high levels of alcohol abuse, commercial sex work, and stigma in healthcare [ 1 , 5 , 6 ]. In our study, men expected partners to be involved in multiple concurrent partnerships, and also they themselves engaged in simultaneous sexual relations.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, qualitative studies have revealed that MSM face stigma based on sexual orientation/behaviour when seeking healthcare services, which has created barriers to timely diagnosis and treatment [ 3 , 4 ]. At the same time, research has shown that sexual risk perceptions and preventive measures might be low among MSM, and high levels of commercial sex work, condomless sex, substance abuse, and depression have been reported [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, associations between sexual stigma and depression have also been well documented in extant literature (Choi et al, 2016;Logie et al, 2012;Wohl et al, 2013). In addition, associations between depression and substance use, as well as sexual risk-taking practices have been documented (Ahaneku et al, 2016;Fletcher & Reback, 2015;Reisner et al, 2009).…”
Section: Discussionmentioning
confidence: 92%
“…The co-occurrence of psychological and physical illness has been found globally in rich, middle-income, and low-income countries, such as Kenya 8. Given the high prevalence of HIV in sub-Saharan Africa,9 it is especially important to assess psychological disorders, for instance depression,10 and even difficulty with coping skills in response to negative daily life events,11 as these can affect behaviors that place people at higher risk for HIV and other sexually transmitted infections (STIs). Moreover, persons infected with HIV who also have depression or other psychological disorders have difficulty with self-care, which includes medication adherence12 and successful participation in a linkage to care intervention 13…”
Section: Introductionmentioning
confidence: 99%